Pengaruh Model Pembelajaran Kooperatif Tipe Pair Check Terhadap Kemampuan Pemahaman Konsep Matematika Peserta Didik Kelas VIII SMPN29 Padang - MUHAMMAD IRHAM (Jurnal Edukasi dan Penelitian Matematika, 2019)
Understanding Mathematical Concepts of  students in class VIII of SMPN  29 Padang is stillAlow. This cannbe seen at the time of observation and the low value of the test given to students which includes indicators of the ability to understand Mathematics Concepts. The solution to this problem is to apply the Pair Check cooperative learning model. The purposeeof this studyyis to find out and describe whether the ability to understand MathematicallConcepts of students whoolearn to use the cooperativeeelearning model Pair Check type issbetter than the ability UnderstandinggMathematical Concepts of students who learn to use direct learning models . This type of research is quasi-experimental and descriptive with a Randomized Control-Group Only Design study design. The study population was class VIII students of SMP 29 Padang in the academic year 2018/2019. The research sample was class VIII.7 as the experimental class and class VIII.4 as the control class. The instrument in this study is the test of the ability to understand Mathematics Concepts. The final test was analyzed using the t-test. Based on the final test analysis obtained P-value = 0.016 less than, meaning that Understanding Mathematics Concepts students who learn with the Pair Check type learning model are better than UnderstandinggMathematical Conceptsoof students who learn with direct learning models. Keywords -. Understandinggmathematical concept, Cooperativeelearning modeloof Pair Check type, Direct learning model